Keterampilan Pembuatan Telor Asin untuk Meningkatkan Kepercayaan Diri pada Warga Binaan BRSBKL Sleman - Ema Julia; Sri Afriyani (Altruism: The Indonesian Journal of Community Engagement, 2023)
The aim of writing about salted egg making skills to increase self-confidence in BRSBKL Sleman assisted residents is to provide insight into how this activity can be an effective means of empowerment and their personal development. The subject of this writing is residents assisted by BRSBKL Sleman, while the object is the skill of making salted eggs to increase self-confidence. Participation in developing food processing skills, especially the activity of making salted eggs, has had a positive impact on the inmates. Apart from developing practical skills related to making salted eggs, this activity also strengthens social interaction and communication skills. Providing opportunities for them to fill their free time with productive activities, this activity increases feelings of achievement and new knowledge regarding the process of making salted eggs. In conclusion, making salted eggs through developing food processing skills has proven to be an effective means of empowering residents assisted by BRSBKL Sleman, integrating practical benefits with the development of social and psychological aspects.